1979
DOI: 10.1002/bip.1979.360181007
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic degradation of β(1 → 4) xylan single crystals

Abstract: SynopsisThe enzymatic degradation of p(1-4) xylan single crystals with xylanases was investigated by electron microscopy and electron diffraction. The enzyme attack takes place a t the edge of the crystals and progresses towards their centers. This is consistent with an endo-enzyme mechanism, where the enzyme interacts essentially with the accessible xylan chains located a t the crystal periphery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

1980
1980
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 8 publications
1
26
0
Order By: Relevance
“…The above observations are highly reminiscent of those made in an earlier investigation on the digestion of xylan crystals by an endo‐xylanase [25]. In that system, the digestion was far slower, but the resulting images displayed the same type of lace‐like morphology together with a preservation of the mono‐crystalline diffraction pattern as shown here.…”
Section: Resultssupporting
confidence: 84%
“…The above observations are highly reminiscent of those made in an earlier investigation on the digestion of xylan crystals by an endo‐xylanase [25]. In that system, the digestion was far slower, but the resulting images displayed the same type of lace‐like morphology together with a preservation of the mono‐crystalline diffraction pattern as shown here.…”
Section: Resultssupporting
confidence: 84%
“…The enzymatic degradation of single crystals has been investigated in the field of polysaccharide. Chanzy et al 7) studied the enzymatic degradation of b (1 e 4)xylan single crystals with xylanases, on the basis of electron micrographs and diffraction patterns, and suggested that endo-type enzymatic attack took place from the edges of crystals toward their centers. The digestion of lamellar single crystals of nigeran with mycodextranase was reported by Marchessault et al 8) ; endo-type attack occurred on the disordered surfaces of single crystals, which had increasing mobility as temperature was raised.…”
Section: Biodegradation Of Single Crystalsmentioning
confidence: 99%
“…Lamellar single crystals are very useful model substrates to elucidate the mechanism of enzymatic degradation on the crystal regions, and the morphological study on the degradation of single crystals is a desirable way which has been performed by the research groups of Marchessault, Chanzy, and Iwata [7][8][9][10][11][12][13] . In the case of aliphatic polyesters, which have many kinds of crystalline modifications and molecular conformations, morphological and electron diffraction studies of single crystals are of importance in elucidating these crystal structures in detail, in addition to the understanding of the degradation mechanism of crystal regions.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Polymer degradation occurs primarily in the hydrolyzable backbone linkages of the polymer chain, leading to a lower molecular weight and eventually to monomer regeneration. Well-known hydrolyzable polymers are polysaccharides, 1 polyesters, 2,7 poly(amino acids), 2 and polyanhydrides.…”
Section: Introductionmentioning
confidence: 99%